A Methods engineering study on Atlantic Steel Corporation - Abalos, Maria Lourdes; Caballes, Christian; Nadal, Germmalyn; Pe, Jonna (Diliman, Quezon City College of Engineering, 2002)
A Methods Engineering study was conducted on Atlantic Steel Corporation, a manufacturing plant concerned with the production of steel rods. The company is one of the only few steel manufacturing plants in the Philippines whose primary focus is to provide good quality steel rods at a competitive price. The company has two melting plants in Taguig and Pasig and a processing plant in Novaliches. The sales office is located at the Galleria Suites, Ortigas Center, Mandaluyong Plant. The project city is concerned with the identification of some of the problems encountered by the plant, the determination of the possible causes of these problems and eventually, generating alternatives and implementation plans. The project proponents concentrated on the production of steel rods due to its complexity and higher probability for enhancement. The study concentrated on the possible causes of material wastage during processing. This is caused mainly by two factors excessive cutting specifications and uninspected deformed or contaminated billets which tend to cause clogging in the rollers. Since the plant has a continuous linear production, the whole operation stops when one of the machines malfunctions. As a result, both time and money are wasted. The objective therefore is to find ways to minimize, if not completely eradicate material wastage. Billets are subjected to head and tail cuts to cut away deformed parts of the billets. Although this would greatly prevent clogging, parts of the billet which are deformed are oftentimes cut off. As a result, scrap due to excessive cutting specifications are generated. The project proponents suggested that a new, more efficient sensor which can detect deformations of billets should be purchased. The plant acquires its raw materials from its two melting plants. The quality of the billets delivered are therefore, oftentimes overlooked. To address this problem, the researchers suggest that a strict quality measure be imposed and that raw materials be inspected in the receiving area.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis